Low-temperature-rise, high-impermeability and low-carbon concrete nano-fluid admixture as well as preparation method and application thereof
By using the prepared low-temperature, high-impermeability, and low-carbon concrete nanofluid additives in cement-based materials, the problems of excessive release of hydration heat, poor anti-permeability, and insufficient mechanical properties of cement-based materials are solved, achieving lower The heat of hydration, higher impermeability and significant improvement in mechanical properties.
Patent Information
- Application Number
- CN202410952298.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-16
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-07-16
AI Technical Summary
Existing cement-based materials such as concrete face problems such as fast hydration heat release, poor permeability and insufficient mechanical properties.
A low-temperature, high-impermeability, low-carbon concrete nanofluid admixture is used. The admixture is composed of water, graphene and dispersants (such as polyvinyl alcohol and sodium carboxymethyl cellulose), and is exfoliated through shearing and emulsification. The combined preparation method significantly improves the dispersion and performance of graphene.
Effectively reduce the hydrophilic release rate of cement base materials, improve the resistance and durability of anti -penetration, and significantly enhance the mechanical properties, including compressive strength and bending strength.
Smart Images

Figure CN119349919A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of graphene materials, and in particular to a low-temperature rise, high impermeability, low-carbon concrete nanofluid admixture, and a preparation method and application thereof. Background Art
[0002] Cement-based materials such as concrete are widely used in construction projects, but they often face problems such as too fast hydration heat release, poor permeability resistance and insufficient mechanical properties. Traditional additives such as silicate admixtures or modifiers can improve these problems to a certain extent, but their effects are still limited, especially when mechanical properties are required to be improved while meeting other multiple requirements.
[0003] Therefore, the prior art still needs to be improved and developed. Summary of the invention
[0004] Based on the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a low-temperature rise, high impermeability, low-carbon concrete nanofluid admixture and a preparation method and application thereof, aiming to solve the problems of existing cement-based materials such as concrete hydration heat release too fast, poor impermeability and insufficient mechanical properties.
[0005] The technical solution of the present invention is as follows:
[0006] In a first aspect of the present invention, a method for preparing a nanofluid admixture is provided, wherein the nanofluid admixture comprises water, graphene dispersed in the water, and a dispersant, wherein the dispersant comprises polyvinyl alcohol and / or sodium carboxymethyl cellulose, and the method for preparing the nanofluid admixture comprises the following steps:
[0007] Provide graphite powder and dispersant;
[0008] Adding the dispersant into water and stirring to obtain a dispersant solution;
[0009] Adding the graphite powder to the dispersant solution, and then sequentially performing shear exfoliation and emulsification exfoliation to obtain a mixed solution;
[0010] After the mixed solution is centrifuged, the supernatant is collected to obtain the nanofluid additive.
[0011] In the present invention, graphene nanofluids with excellent thermal conductivity and mechanical strength are added to cement-based materials as admixtures, which can be effectively dispersed in the cement-based system, effectively absorb and disperse the hydration heat release during the cement hydration process, slow down the hydration reaction rate, and thus reduce the overall hydration heat. At the same time, the high surface area and two-dimensional structure of graphene help fill the microscopic pores of cement-based materials, improve their impermeability and durability, and significantly enhance the mechanical properties of cement-based materials (including compressive strength and flexural strength, etc.).
[0012] In addition, graphene often faces the following problems in civil engineering applications: 1. Cost issues: Currently, the production of high-quality graphene is still an expensive process, which limits its application in large-scale civil engineering projects. 2. Production scale: Large-scale production of high-quality graphene is still a challenge. Current production methods can usually only obtain a limited amount of graphene, and the inability to expand the scale limits its application in the field of civil engineering. 3. Interface compatibility: The interface compatibility of graphene with traditional building materials is an important issue. The binding performance of graphene with building materials such as cement and concrete needs to be improved to ensure its effective application in civil engineering. However, the present invention uses graphite powder (which can be industrial grade) as a raw material to prepare a nanofluid admixture to replace the more expensive commercial graphene, effectively reducing the cost. Using a liquid phase exfoliation method, specifically a combination of shear exfoliation and emulsification exfoliation, the preparation of a nanofluid admixture is not only efficient and suitable for expansion to large-scale production, but also the graphene in the nanofluid admixture can be stably dispersed and can be directly used for cement mixing, which enhances the feasibility of industrial application. By introducing water-soluble polymers (vinyl alcohol and / or sodium carboxymethyl cellulose), which can act as surfactants, the interfacial compatibility of graphene with cement-based materials is enhanced, and its dispersibility and performance are improved, thereby effectively solving the difficult problems of graphene application in civil engineering and enhancing its feasibility and practicality in this field.
[0013] In the present invention, shear exfoliation induces relative sliding between graphite layers, thereby introducing initial exfoliation between graphite sheets, reducing the van der Waals forces between graphite sheets, and thus providing graphite sheets that are easier to exfoliate for the subsequent emulsification exfoliation process. In addition, shear exfoliation also helps to break the strong interactions between graphite sheets, increases the exfoliable surface area of graphene, and enables the shear force in the emulsification exfoliation stage to act more efficiently on the exfoliation process of graphene. Therefore, the two-step processing strategy of shear exfoliation combined with emulsification exfoliation significantly improves the release and yield of graphene.
[0014] Specifically, shear stripping relies on the turbulence effect generated by high-speed rotating blades. The significant increase in local shear force and the improvement in fluid mixing efficiency under turbulent conditions enhance the interaction and shear effect between graphene sheets, promoting the effective separation of graphene sheets. In addition, microscopic vortices and high shear regions in turbulence help overcome the van der Waals attraction between graphene sheets, further improving the stripping efficiency and dispersibility of graphene.
[0015] In some embodiments, the concentration of the dispersant in the dispersant solution is 5 to 25 g / L. As the concentration of the dispersant (i.e., surfactant) increases, the surface tension decreases, resulting in more dispersant molecules being adsorbed onto the liquid-gas interface. The adsorption of dispersant molecules can significantly reduce the surface tension, so the adsorption amount per unit area will increase with the increase of concentration. However, once a certain concentration (i.e., critical micelle concentration) is reached, the surface is already saturated, and the surface tension will not change significantly due to the increase in concentration, or even no longer increase. Therefore, the concentration of graphene in the final nanofluid admixture shows an upward trend as the concentration of the dispersant increases, and will not rise again after reaching a certain concentration. However, too much dispersant will affect the performance of cement-based materials. Within this concentration range, it can be ensured that the concentration of graphene in the prepared nanofluid admixture remains at a high level without affecting the performance of cement-based materials too much.
[0016] In some embodiments, the rotation speed of the shear stripping is 10000 rpm, and the time of the shear stripping is 3 to 21 min (for example, it can be 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20 or 21 min, etc.).
[0017] In some embodiments, the rotation speed of the emulsification peeling is 6000 rpm, and the time of the emulsification peeling is 20 to 180 min (for example, it can be 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170 or 180 min, etc.).
[0018] In some embodiments, the centrifugation speed is 10000 rpm, and the centrifugation time is 30 to 80 min (eg, 30, 40, 50, 60, 70 or 80 min, etc.).
[0019] In some embodiments, the shear peeling is performed for 12 minutes, the emulsification peeling is performed for 120 to 140 minutes, and the centrifugation is performed for 30 minutes.
[0020] The second aspect of the present invention provides a nanofluid additive, wherein the nanofluid additive is prepared by the preparation method of the present invention as described above.
[0021] The third aspect of the present invention provides an application of the nanofluid admixture of the present invention as described above, wherein the nanofluid admixture is applied to a cement-based material, and the cement-based material includes one of cement paste, cement mortar, and concrete.
[0022] A fourth aspect of the present invention provides a modified cement-based material, wherein the modified cement-based material comprises one of modified cement paste, modified cement mortar, and modified concrete;
[0023] The modified cement paste comprises cement, water and the nanofluid admixture of the present invention as described above;
[0024] The modified cement mortar comprises cement, sand, water and the nanofluid admixture of the present invention as described above;
[0025] The modified concrete is prepared from the modified cement paste or the modified cement mortar.
[0026] In some embodiments, in the modified cement paste, the mass ratio of the cement, water and graphene in the nanofluid admixture is 1:(0.45-0.55):(0-0.002); in the modified cement mortar, the mass ratio of the cement, sand, water and graphene in the nanofluid admixture is 1:(2-4):(0.45-0.55):(0-0.002); in the modified cement paste and the modified cement mortar, the mass of graphene in the nanofluid admixture is not 0. That is, the mass of graphene in the nanofluid admixture accounts for 0% to 0.2% of the mass of cement, but not 0%.
[0027] Beneficial effects: In the present invention, graphene nanofluid with excellent thermal conductivity and mechanical strength is added to cement-based materials as an admixture, which can be effectively dispersed in the cement-based system, can effectively absorb and disperse the hydration heat release during the cement hydration process, slow down the hydration reaction rate, and thus reduce the overall hydration heat. At the same time, the high surface area and two-dimensional structure of graphene help to fill the microscopic pores of cement-based materials, improve their impermeability and durability, and significantly enhance the mechanical properties of cement-based materials, including compressive strength and flexural strength. In addition, the present invention uses graphite powder (which can be industrial grade) as a raw material to prepare nanofluid admixtures to replace the more expensive commercial graphene, effectively reducing costs. Using a liquid phase exfoliation method, specifically a combination of shear exfoliation and emulsification exfoliation, the preparation of nanofluid admixtures is not only efficient and suitable for expansion to large-scale production, but also the graphene in the nanofluid admixture can be stably dispersed and can be directly used for cement mixing, enhancing the feasibility of industrial applications. By introducing water-soluble polymers (vinyl alcohol and / or sodium carboxymethyl cellulose), which can act as surfactants, the interfacial compatibility of graphene with cement-based materials is enhanced, and its dispersibility and performance are improved, thereby effectively solving the difficult problems of graphene application in civil engineering and enhancing its feasibility and practicality in this field. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1(a) is the appearance of the first nanofluid admixture prepared in Example 1 on the first day and after standing for 180 days; (b) is the appearance of the nanofluid admixture prepared in Example 2 under the conditions of 350 mL of CMC solution, shear stripping for 12 minutes, and emulsification stripping for 40 minutes on the first day and after standing for 180 days.
[0029] Figure 2 (a) is a TEM image of the third nanofluid admixture prepared in Example 1, (b) is a TEM image of the nanofluid admixture prepared in Example 2 under the conditions of 350 mL of CMC solution, shear stripping for 12 min, and emulsification stripping for 40 min, (c) is an enlarged image of a certain area of Figure (a), (d) is an enlarged image of a certain area of Figure (b), (e) is a diffraction spot image of the third nanofluid admixture prepared in Example 1, and (f) is a diffraction spot image of the nanofluid admixture prepared in Example 2 under the conditions of 350 mL of CMC solution, shear stripping for 12 min, and emulsification stripping for 40 min.
[0030] Figure 3 The AFM results of the second nanofluid admixture prepared in Example 1 are shown, wherein (a) is the AFM morphology image at one position, (b) is the AFM morphology image at another position, (c) is the height curve corresponding to (a), and (d) is the height curve corresponding to (b).
[0031] Figure 4 The XPS results of the second nanofluid additive prepared in Example 1 are shown in Figure 1, where (a) is the overall spectrum, (b) is the C1s spectrum, and (c) is the O1s spectrum.
[0032] Figure 5 The linear relationship diagram of the absorbance obtained in Example 1 as a function of graphene concentration.
[0033] Figure 6 This is a graph showing the concentration results of graphene in the four nanofluid additives prepared in Example 1.
[0034] Figure 7 This is a graph showing the graphene concentration changing with emulsification stripping time in Example 1.
[0035] Figure 8 This is a graph showing the change in the yield of graphene by emulsification exfoliation as a function of the emulsification exfoliation time in Example 1.
[0036] Fig. 9 This is a graph showing the graphene concentration results in 30 nanofluid additives in Example 2.
[0037] Fig.10(a) is a curve chart showing the change of graphene concentration in PVA-GNAs with centrifugation time in Example 3, and (b) is a curve chart showing the change of graphene concentration in CMC-GNAs with centrifugation time in Example 3.
[0038] Fig.11 This is a graph showing the effect of the nanofluid admixture prepared with PVA on the strength of cement mortar without centrifugation and after 30 minutes of centrifugation.
[0039] Fig.12 This is a graph showing the initial setting time and final setting time of PVA-GNAs modified cement paste with different graphene mass contents in Example 4.
[0040] Fig.13 This is a graph showing the initial setting time and final setting time of CMC-GNAs modified cement paste with different graphene mass contents in Example 5.
[0041] Fig.14 This is a hydration exothermic rate curve of PVA-GNAs modified cement slurry with different graphene mass contents in Example 6.
[0042] Fig.15 This is the hydration heat release rate curve of cement paste when PVA is added alone.
[0043] Fig.16 This is the cumulative hydration exotherm curve of the PVA-GNAs modified cement paste in Example 6.
[0044] Fig.17 (a) is the hydration exothermic rate curve of the net CMC-GNA modified cement in Example 6, and (b) is the cumulative hydration exothermic curve of the net CMC-GNA modified cement in Example 6.
[0045] Fig.18 (a) is a graph showing the flow velocity test results of the PVA-GNAs modified cement mortar in Example 7, and (b) is a graph showing the flow velocity test results of the CMC-GNAs modified cement mortar in Example 7.
[0046] Fig.19 (a) is a graph showing the compressive strength test results of the PVA-GNAs modified cement mortar in Example 8, and (b) is a graph showing the compressive strength test results of the CMC-GNAs modified cement mortar in Example 8.
[0047] Fig. 20 (a) is the flexural strength test result of PVA-GNAs modified cement mortar in Example 8, and (b) is the flexural strength test result of CMC-GNAs modified cement mortar in Example 8.
[0048] Fig.21 These are SEM images of PVA-GNAs modified cement mortar with different graphene mass contents after curing in Example 9, where (a) is 0.02%, (b) is 0.04%, (c) is 0.06% and (d) is 0.08%.
[0049] Fig. 22 These are SEM images of CMC-GNAs modified cement mortars with different graphene mass contents after curing in Example 9, where (a) is 0.02% and (b) is 0.04%.
[0050] Fig.23 These are SEM images of the CMC-GNAs modified cement mortar with different graphene mass contents after curing in Example 9 under the backscattering mode at a scale of 100 μm, where (a) is 0%, (b) is 0.02%, (c) is 0.04%, (d) is 0.06%, (e) is 0.08%, and (f) is 0.10%.
[0051] Fig.24 These are SEM images of the CMC-GNAs modified cement mortar with different graphene mass contents after curing in Example 9 under the backscattering mode at a scale of 500 μm, where (a) is 0%, (b) is 0.02%, (c) is 0.04%, (d) is 0.06%, (e) is 0.08%, and (f) is 0.10%.
[0052] Fig.25 (a) is a graph showing the relationship between the cumulative pore volume and pore size (adsorption branch) of the CMC-GNAs modified cement mortar in Example 10, and (b) is a graph showing the pore size distribution curve (adsorption branch) of the CMC-GNAs modified cement paste in Example 10.
[0053] Fig.26 (a) is a curve showing the relationship between the chloride ion concentration in the test block and the corresponding depth after 60 days of salt water immersion in Example 11, and (b) is a curve showing the relationship between the chloride ion concentration in the test block and the corresponding depth after 120 days of salt water immersion in Example 11. DETAILED DESCRIPTION
[0054] The present invention provides a nanofluid additive and a preparation method and application thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0055] Unless otherwise defined, all technical terms and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0056] The present invention will be further described below by means of specific examples.
[0057] The information of some equipment and raw materials used in the following examples is as follows:
[0058] Graphene powder: 100 mesh, industrial grade; polyvinyl alcohol (PVA) powder: Mw=90000, industrial grade; sodium carboxymethyl cellulose (CMC) powder: Mw=90000.
[0059] Mixer: Home mixer, Philips HR2096. Emulsifier: Silverson L5 series emulsifier. Centrifuge: Desktop high-speed centrifuge, Xiangli TG16-WS.
[0060] Example 1
[0061] The first method for preparing the nanofluid admixture comprises the following steps:
[0062] (1) PVA powder was added to water, which was then heated on a constant temperature magnetic stirrer at 80° C. and stirred for 24 h to ensure that the powder was completely dissolved to form a uniform PVA solution (wherein the concentration of PVA was 14.3 g / L).
[0063] (2) 350 mL of PVA solution was taken, 21.4 g of graphite powder was added thereto, and then shearing and exfoliating was performed in a blender at a rotation speed of 10,000 rpm for 6 min, and then emulsifying and exfoliating was performed in an emulsifying disperser at a rotation speed of 6,000 rpm for 60 min to obtain a mixed solution;
[0064] (3) The mixed solution is placed in a centrifuge and centrifuged at 10,000 rpm for 30 minutes, and the supernatant is collected to obtain the nanofluid admixture.
[0065] The preparation method of the second nanofluid admixture is different from that of the first nanofluid admixture only in that the shear stripping time in step (2) is 12 minutes.
[0066] The preparation method of the third nanofluid admixture differs from the first nanofluid admixture only in that the volume of the PVA solution in step (2) is 1600 mL and the shear stripping time is 12 min;
[0067] The preparation method of the fourth nanofluid admixture is different from that of the first nanofluid admixture only in that the shear stripping time in step (2) is 0 min, for comparison.
[0068] test:
[0069] (1) The dispersion stability of the nanofluid admixture was tested by static observation method as follows:
[0070] The above nanofluid admixtures were placed in sample bottles, and then left to stand at room temperature. The appearance changes at different time points were recorded and observed. After 180 days, the appearance of the first, second and third nanofluid admixtures remained unchanged, indicating that the graphene in the nanofluid admixture prepared by the preparation method provided by the present invention has good dispersion stability. Taking the first nanofluid admixture as an example, the appearance of the first day and the 180th day are as follows: Figure 1 As shown in (a).
[0071] (2) The third nanofluid admixture was tested by transmission electron microscopy (TEM). The results are as follows: Figure 2 As shown. Figure 2 As shown in (a), the graphene nanosheet has a wrinkled transparent layered structure with clearly visible edges, reflecting its layered two-dimensional nanomaterial characteristics. Figure 2 As shown in (c), the enlarged view shows the obvious edge of the single-layer graphene, which further proves that the number of graphene layers in the nanofluid admixture is controlled at a low level. Figure 2 As shown in (e), the diffraction pattern of graphene shows its hexagonal lattice structure, indicating that the prepared graphene has good crystal quality.
[0072] (3) Atomic force microscopy (AFM) test was performed on the second nanofluid admixture. The results are as follows: Figure 3 As shown, it can be seen that the linear size of graphene is distributed in 1-5μm, and it can be seen from the height curve and the morphology that it is a folded graphene nanosheet. The graphene interlayer spacing is 0.335nm, and the heights of the flakes in the AFM morphology image measured in this embodiment are 0.352nm and 0.682nm, respectively, which indicates that the AFM has captured the single-layer graphene and double-layer graphene present in the nanofluid additive.
[0073] (4) X-ray photoelectron spectroscopy (XPS) test was performed on the second nanofluid admixture. The results are as follows: Figure 4 As shown. Figure 4 The total spectrum in (a) shows C1s and O1s peaks, which indicates that the sample contains PVA because PVA itself contains a large amount of carbon and oxygen elements. Figure 4The C1s peak in (b) is analyzed and located at about 284.5 eV, which is the sp 2 The sign of hybridized carbon indicates that there are a large number of graphene structures in the tested sample. CO bonds appear at a binding energy of 286eV, and CC bonds appear at 284eV. These bonds are chemical bonds in PVA molecules, indicating that no new chemical bonds appear between graphene and PVA, and the connection between graphene and PVA is a non-covalent bond. Therefore, during the centrifugal stripping and emulsification stripping process, PVA did not change the structure of graphene and did not introduce other structural defects to graphene. Figure 4 The O1s peak in (c) is analyzed. The presence of the O1s peak usually indicates that there are oxides or functional groups with high oxygen content on the sample surface, such as hydroxyl groups. The hydroxyl groups in PVA produce an O1s peak in the XPS spectrum, which is located at 531-533 eV.
[0074] (5) The graphene concentration of the four nanofluid additives was tested as follows:
[0075] a. Preparation of graphene powder: Add 120mL of the second nanofluid additive to the crucible, and then place it in a high-temperature furnace for high-temperature treatment to remove the moisture and PVA in it. Among them, the high-temperature treatment program is set as follows: the temperature rises from room temperature (25°C) to 250°C within 1 hour; maintains at 250°C for 3 hours; then heats to 500°C within 30 minutes; maintains at 500°C for 2 hours; finally, let the temperature fall back to room temperature. After the temperature falls back to room temperature, take out the crucible, and the black powder in it is graphene powder. The detailed reaction process is as follows:
[0076] Water evaporation (initial, close to 100°C):
[0077] H2O(l)→H2O(g) (Formula 1)
[0078] PVA dehydration reaction (200-300℃):
[0079] [-CH2CH(OH)-] n →[-CH=CH-] n +nH2O (Formula 2)
[0080] The main chain of PVA breaks (further heated to 300-400℃):
[0081] [-CH2CH(OH)-] n →CH3COOH+CH3OH+…(Formula 3)
[0082] Further pyrolysis and cracking reactions (400-500 °C), as the temperature further increases, PVA and its cracking products may undergo more complex chemical changes, including further cracking, condensation and cyclization reactions, and may form more different types of small molecular compounds, such as olefins, alkynes, aromatic compounds, etc.
[0083] Carbonization reaction (approaching 500°C or higher): At higher temperatures, especially in the presence of oxygen, residual organic matter is converted into gas:
[0084] Organic matter → H2O(g)+CO+CO2+… (Formula 4)
[0085] b. Preparation of graphene aqueous dispersions of different concentrations: 0.01 g, 0.025 g, 0.05 g, 0.075 g, and 0.1 g of the graphene powder prepared above were weighed respectively, mixed with 100 mL of deionized water, and ultrasonicated for 10 min to obtain graphene aqueous dispersions with concentrations of 0.1 g / L, 0.25 g / L, 0.5 g / L, 0.75 g / L, and 1.0 g / L, respectively.
[0086] c. Establishing the linear relationship between graphene concentration and absorbance: Using a UV-visible spectrometer, the absorbance of the above-mentioned graphene aqueous dispersions with different concentrations was measured at a wavelength of 660nm. Based on this, a standard curve of concentration and absorbance was drawn, showing that there is a linear relationship between the two. The results are as follows: Figure 5 The linear regression equation is A=0.506C+0.04, where A represents absorbance and C represents graphene concentration.
[0087] d. By measuring the absorbance of the four nanofluid additives at a wavelength of 660 nm, and then substituting it into the above linear regression equation, the concentration of graphene in the four nanofluid additives can be measured. The results are as follows: Figure 6 shown.
[0088] The results show that under the same solution volume (350mL), the yield of graphene can be significantly improved by pre-shear exfoliation for 6 minutes followed by emulsion exfoliation. Compared with the sample that was directly emulsion exfoliated without pre-shear exfoliation, the graphene yield of pre-shear exfoliation + emulsion exfoliation is more than twice as high. This shows that the pre-shear exfoliation process introduces initial exfoliation between graphite sheets, reducing the van der Waals force between graphite sheets, thereby providing easier-to-exfoliate graphite sheets for the subsequent emulsion exfoliation process. In addition, pre-shear exfoliation also helps to break the strong interaction between graphite sheets, increase the exfoliable surface area of graphene, and make the shear force in the emulsion exfoliation stage act on graphene more efficiently. Therefore, the two-step treatment of shear exfoliation combined with emulsion exfoliation significantly improves the release and yield of graphene.
[0089] In addition, this embodiment also studies the graphene concentration in the nanofluid admixture and the emulsification exfoliation graphene yield after 350mL of PVA solution was subjected to shear exfoliation for 6min and then emulsification exfoliation for different times (0, 20, 40, 60, 80, 100, 120, 140, 160, 180min); the graphene concentration in the nanofluid admixture and the emulsification exfoliation graphene yield after 350mL of PVA solution was subjected to shear exfoliation for 12min and then emulsification exfoliation for different times (0, 20, 40, 6 The graphene concentration in the nanofluid admixture and the graphene yield of emulsified exfoliation were obtained after 1600mL of PVA solution was subjected to shear exfoliation for 12min and then to emulsified exfoliation for different time periods (0, 20, 40, 60, 80, 100, 120, 140, 160, 180min). The graph of graphene concentration changing with emulsified exfoliation time is shown in the figure below. Figure 7 As shown, when the shear stripping time is fixed, before the emulsification stripping time of 120 min is reached, the graphene concentration obtained by the smaller solution volume (350 mL) used in the single preparation process generally exceeds that of the larger solution volume (1600 mL).
[0090] The high-speed rotation of the instrument probe during the shear emulsification process introduces a higher fluid velocity when the solution volume is small, resulting in an increase in the Reynolds number. When the Reynolds number reaches a certain threshold, the fluid changes from laminar flow to turbulent flow. The significant increase in local shear force and the improvement in fluid mixing efficiency in the turbulent state enhance the interaction and shear effect between graphene sheets and promote the effective separation of graphene sheets. In addition, the microscopic vortices and high shear regions in the turbulent flow help to overcome the van der Waals attraction between graphene sheets, further improving the exfoliation efficiency and dispersibility of graphene. Therefore, by adjusting the shear and emulsification conditions to achieve a suitable Reynolds number and transforming laminar flow into turbulent flow, the graphene production process can be optimized and efficient graphene exfoliation and dispersion can be achieved. At this stage, extending the emulsification exfoliation time significantly increased the graphene concentration, indicating that the graphene concentration increases with the increase in emulsification exfoliation time. However, once the emulsification exfoliation time is extended to 120 min, the graphene concentration using a larger solution volume increases slowly but continues to rise, while the graphene concentration using a smaller solution volume tends to be stable or even slightly decreases. This suggests that in the case of a larger solution volume, extending the emulsification time to more than 120 min is more conducive to obtaining a higher graphene concentration, while for a smaller solution volume, the optimal emulsification time does not need to be so long. Therefore, when the goal is to prepare a high-concentration and large-volume nanofluid admixture, the appropriate emulsification time should be set to more than 120 min to obtain a high graphene concentration and yield.
[0091] Although a higher unit concentration of graphene can be achieved in a smaller solution volume used in a single preparation process, from the perspective of total yield, i.e. the product of concentration and solution volume, when a larger solution volume is used in a single preparation, the total yield is not necessarily lower than the output when the solution volume is smaller. Therefore, it is important to further evaluate the overall yield of graphene. The results of the change of emulsification exfoliation graphene yield with emulsification exfoliation time are shown in the figure below. Figure 8 As shown, this yield is obtained by removing the initial concentration increment caused by shear exfoliation from the overall graphene concentration. The results show that shear exfoliation can effectively improve the subsequent emulsification exfoliation yield. In the early stage of the emulsification exfoliation process, although the initial concentration was low, a relatively high yield was observed when a larger solution volume (1600 mL) was used in a single preparation process, which reflects the positive role of shear exfoliation pretreatment in promoting emulsification efficiency. In addition, Figure 8 The yield peak in the late emulsification stripping process was also revealed. This peak appeared at 120 min (350 mL) and 140 min (1600 mL) respectively, depending on the amount of solution used in the single preparation process. The time of the yield peak was delayed as the amount of solution increased. This finding shows that when preparing nanofluid admixtures, using a larger amount of solution can achieve a better yield than using a smaller amount of solution.
[0092] Example 2
[0093] The preparation method of the nanofluid admixture comprises the following steps:
[0094] (1) CMC powder was added to water, and then heated on a constant temperature magnetic stirrer at 80°C and stirred for 24 hours to ensure that the powder was completely dissolved to form a uniform CMC solution (wherein the concentration of CMC was 14.3 g / L).
[0095] (2) Take 10 portions of 350 mL of CMC solution, add 21.4 g of graphite powder respectively, and then shear and peel at a speed of 10000 rpm in a blender for 6 min, and then emulsify and peel at a speed of 6000 rpm in an emulsifier disperser for 0, 20, 40, 60, 80, 100, 120, 140, 160, and 180 min, respectively, to obtain 10 portions of mixed solution;
[0096] (3) The 10 mixed solutions were centrifuged at 10,000 rpm for 30 min, and the supernatant was collected to obtain 10 nanofluid admixtures.
[0097] At the same time, 10 portions of 350 mL of CMC solution were taken to prepare 10 nanofluid admixtures. The only difference from the above steps was that the shear stripping time was 12 min. Then 10 portions of 1600 mL of CMC solution were taken to prepare 10 nanofluid admixtures. The difference from the above steps was that the shear stripping time was 12 min.
[0098] test:
[0099] (1) The dispersion stability of the nanofluid admixture was tested by static observation method, the method was the same as that in Example 1, and after 180 days, the appearance of the nanofluid admixture (except the nanofluid admixture prepared when the shear peeling time was 0) still had no obvious change, indicating that the graphene in the nanofluid admixture prepared by the preparation method provided by the present invention had good dispersion stability. Taking the nanofluid admixture prepared by 350mL of CMC solution, shear peeling for 12min, and emulsification peeling for 40min as an example, the appearance of the nanofluid admixture on the first day and the 180th day was as follows: Figure 1 As shown in (b).
[0100] (2) The TEM results of the nanofluid admixture prepared under the conditions of 350 mL of CMC solution, shear stripping for 12 min, and emulsification stripping for 40 min are shown in Figure 2. Figure 2 As shown in (b), (d) and (f) in the figure, it has a morphology and diffraction spot similar to those of the third nanofluid additive in Example 1.
[0101] (3) The graphene concentration in the above 30 nanofluid additives was tested using the same method as in Example 1. The results are as follows: Fig. 9 As shown, higher graphene concentrations can be obtained under different conditions, and the graphene concentration prepared by CMC under the same conditions is higher than that prepared by PVA in Example 1. In addition, when a large solution volume (1600 mL) is selected for single preparation, the emulsification stripping time is selected as 120 min, which can ensure high yield while optimizing the total yield of graphene.
[0102] Example 3
[0103] The preparation of nanofluid admixture with PVA includes the following steps:
[0104] (1) Provide a PVA solution, the preparation method of which is the same as that of Example 1.
[0105] (2) 6 portions of 350 mL of PVA solution were taken, 21.4 g of graphite powder was added thereto respectively, and then shearing and exfoliating were performed in a blender at a speed of 10,000 rpm for 12 min, and then emulsifying and exfoliating were performed in an emulsifying disperser at a speed of 6,000 rpm for 120 min, respectively, to obtain 6 portions of mixed solution;
[0106] (3) The six mixed solutions were centrifuged at 10,000 rpm for 30, 40, 50, 60, 70, and 80 min, respectively, and the supernatants were collected to obtain six nanofluid admixtures, which were recorded as six PVA-GNAs.
[0107] The method for preparing nanofluid admixtures using CMC is as follows: repeat the above steps, except that in step (1), the PVA is replaced by CMC, thereby obtaining 6 nanofluid admixtures, which are recorded as 6 CMC-GNAs.
[0108] The graphene concentration in PVA-GNAs and CMC-GNAs was tested. Fig.10 As shown in the figure, the length of centrifugation time directly affects the separation efficiency of graphene sheets from other components in the solution, and thus affects the final concentration of graphene. After 50 minutes of centrifugation, the graphene concentration in the nanofluid admixture is almost maintained at a constant level, which indicates that the graphene sedimentation velocity is close to 0 at this time, and the density of the graphene particles and the medium is very close, so the downward gravity and upward buoyancy of the particles are basically offset, that is, the nanofluid admixture has been completely centrifuged. Using Stokes' law, it can be seen that higher medium viscosity will lead to slower sedimentation velocity, so it can be explained that PVA and CMC can sufficiently increase the viscosity of the medium, thereby slowing down the sedimentation velocity of graphene, so that it reaches equilibrium after 50 minutes. In addition, since the sedimentation velocity tends to 0 after 50 minutes, it shows that PVA-GNAs and CMC-GNAs can form a stable graphene dispersion system, and even under the centrifugal force of 10,000 rpm, the graphene particles can remain suspended without sedimentation. The present invention fully considers the large-scale application of nanofluid admixtures, so the selected graphite powder raw materials are all industrial grade, which requires the stability and reproducibility of the process. The trade-off between efficiency and cost is crucial, and the selection of a centrifugation time of 30 minutes is more in line with the actual conditions of industrial production. Shorter centrifugation time can significantly reduce energy consumption and operation time, which can reduce costs in mass production. The nanofluid admixture prepared with PVA, the effect of the nanofluid admixture obtained without centrifugation and after 30 minutes of centrifugation on the strength of cement mortar is shown in the following figure. Fig.11As shown in the results, in the 28-day strength test of cement mortar, the centrifugation time of 30 minutes has little effect on the compressive strength, but the improvement of the flexural strength is relatively significant. This shows that a good balance has been found between performance and cost. In addition, in cement-based materials, graphene should not only improve mechanical properties, but also provide multiple potential functions such as electrical conductivity and thermal conductivity. Excessive centrifugation may destroy the overlap and interconnection between graphene sheets, which is not conducive to the formation of an effective conductive network or the enhancement of the mechanical properties of composite materials. Moderate centrifugation time helps to retain these structural features. The uniform dispersion of graphene in cement-based materials is key, but there is no need to excessively pursue marginal effects. Moderately centrifuged graphene is easier to disperse in cement-based materials, while excessive centrifugation may cause it to re-aggregate in cement-based materials, thereby affecting the final performance of the material. In addition, cement-based materials generally do not require ultra-high purity graphene. Graphene aggregates or multilayer structures may be more conducive to enhancing the performance of materials to a certain extent. Excessive centrifugation time may also have a negative impact on the quality of graphene, such as oxidation or structural damage.
[0109] From the results of Examples 1, 2 and 3 above, it can be seen that the connection between graphene and PVA (or CMC) is a non-covalent bond, and the use of the dispersant does not introduce additional structural defects. The combined process of shear exfoliation for 12 min + emulsification exfoliation for 120 to 140 min has the highest efficiency for the preparation of graphene. Considering practical applications and cost-effectiveness, 30 min is selected as the optimal parameter for centrifugation time.
[0110] Example 4 Application of Nanofluid Admixture (PVA-GNAs) in Increasing Final Setting Time of Cement Paste
[0111] (1) Nanofluid admixtures (PVA-GNAs) with different graphene mass concentrations (0.025%, 0.050%, 0.075%, 0.100%, 0.125%, 0.150%, 0.175%, 0.200%) were prepared using PVA solution. The preparation method is as described above.
[0112] (2) PVA-GNAs were added to cement paste to prepare modified cement paste (referred to as PVA-GNAs modified cement paste): the modified cement paste included cement, water, defoamer TBP (tributyl phosphate) and nanofluid admixtures with different graphene mass concentrations; the mass ratios of cement, water, defoamer TBP and graphene in the nanofluid admixture were 1:0.45:0.006:0. 025%, 1:0.45:0.006:0.050%, 1:0.45:0.006:0.075%, 1:0.45:0.006:0.100%, 1:0.45:0.006:0.125%, 1:0.45:0.006:0.150%, 1:0.45:0.006:0.175%, 1:0.45:0.006:0.200%.
[0113] The mixing process of PVA-GNAs modified cement paste is: low speed mixing for 60s → stop mixing for 60s → high speed mixing for 60s → stop mixing → vibrate for 60s. After completing the mixing process of PVA-GNAs modified cement paste, the PVA-GNAs modified cement paste is immediately sent to the automatic Vicat instrument for the determination of the setting time, so as to accurately determine the initial setting time and the final setting time. The results are as follows Fig.12As shown (the 0.000 group is also the blank control group, which means that no nanofluid admixture is added), it can be seen that the nanofluid admixture helps to slow the setting of cement paste. Specifically, with the increase of graphene dosage, the initial setting and final setting time of cement paste are significantly extended. Specifically, the initial setting time of the blank control group is 210min and the final setting time is 555min, which is extended to the initial setting time of the group with the highest graphene dosage (0.200%) of 300min and the final setting time is 735min. PVA plays a key retarding role in cement paste. PVA not only increases the viscosity of cement paste by interacting with the surface of cement particles, but also "captures" water molecules and cement particles by forming a network structure, thereby slowing down the rate of hydration reaction. This retarding effect is due to the fact that the PVA molecular chain can form a physical barrier in the cement paste that hinders the free movement and reaction of water molecules and cement particles, resulting in an extension of the setting time. The addition of graphene brings about a nucleation effect. Due to its extremely high specific surface area, it can provide a large number of nucleation sites, which theoretically helps to accelerate the occurrence of hydration reactions. The high-energy sites on the graphene surface adsorb water molecules, providing an optimized local environment for the formation of hydration products, which theoretically should be able to promote the acceleration of the setting process. However, in the modified cement paste, the retarding effect of PVA and the nucleation effect of graphene form a complex competitive relationship. On the one hand, the retarding effect of PVA slows down the hydration reaction rate and prolongs the setting time; on the other hand, the nucleation effect of graphene attempts to accelerate this process. With the increase of graphene content, this competitive relationship leads to the extension of initial and final setting times, especially the extension of final setting time is more significant. This phenomenon occurs mainly because, although graphene may promote the occurrence of hydration reaction in the early stage, as the reaction proceeds, the retarding effect of PVA gradually dominates, especially in the later stage of hydration reaction, the influence of PVA becomes more obvious, resulting in a significant extension of final setting time.
[0114] Example 5 Application of Nanofluid Admixture (CMC-GNAs) in Increasing the Final Setting Time of Cement Paste
[0115] (1) Nanofluid admixtures with different graphene mass concentrations (0.02%, 0.04%, 0.06%, 0.080%, 0.10%) were prepared using CMC solution. The preparation method is as described above.
[0116] (2) Adding nanofluid admixture (CMC-GNAs) to cement paste to prepare modified cement paste (referred to as CMC-GNAs modified cement paste): the modified cement paste includes cement, water, defoamer TBP and nanofluid admixture with different graphene mass concentrations; the mass ratios of cement, water, defoamer TBP and graphene in the nanofluid admixture are 1:0.5:0.006:0.02%, 1:0.5:0.006:0.04%, 1:0.5:0.006:0.06%, 1:0.5:0.006:0.08%, and 1:0.5:0.006:0.10%, respectively. The stirring process of CMC-GNAs modified cement paste is the same as that of Example 3.
[0117] After the mixing process of CMC-GNAs modified cement paste is completed, the CMC-GNAs modified cement paste is immediately sent to the automatic Vicat instrument to measure the setting time, so as to accurately determine the initial setting time and the final setting time. Fig.13 As shown in the figure (the 0.00 group is the blank control group, which means that no nanofluid admixture is added), the results show that with the increase of graphene dosage, the initial setting and final setting time of cement paste are significantly prolonged, from the initial setting time of 450min and the final setting time of 705min in the blank control group to the initial setting time of 810min and the final setting time of 1080min in the group with the highest graphene dosage (0.10%). CMC plays a retarding role in cement paste, which is mainly because CMC, as a surfactant, can form an adsorption film on the surface of cement particles. This film not only increases the viscosity of cement paste, but also reduces the rate of hydration reaction. CMC molecules reduce the direct contact between water molecules and cement particles through adsorption on the surface of cement particles, thereby slowing down the hydration process. Similarly, in cement paste, the retarding effect of CMC forms a competitive relationship with the nucleation effect of graphene. Although graphene has the potential to promote hydration, the presence of CMC significantly slows down the overall hydration rate, resulting in an overall extension of the setting time. This competitive relationship makes the increments of initial and final setting times almost the same, 360 min and 375 min respectively, indicating that the effect of CMC maintains a consistent influence throughout the hydration process.
[0118] Example 6 Application of Nanofluid Additives (PVA-GNAs) in Delaying the Hydration Reaction and Reducing the Heat Release Rate
[0119] (1) Nanofluid admixtures with different graphene mass concentrations (0.07%, 0.14%, 0.21%, and 0.28%) were prepared using PVA solution. The preparation method is described above.
[0120] (2) Adding nanofluid admixture (PVA-GNAs) to cement paste to prepare modified cement paste (referred to as PVA-GNAs modified cement paste): the modified cement paste includes cement, water, defoamer TBP and nanofluid admixture with different graphene mass concentrations, wherein the mass ratios of cement, water, defoamer TBP and graphene in the nanofluid admixture are 1:0.45:0.006:0.07%, 1:0.45:0.006:0.14%, 1:0.45:0.006:0.21% and 1:0.45:0.006:0.28%, respectively. The stirring process of PVA-GNAs modified cement paste is the same as that of Example 4.
[0121] The hydration exothermic rate curves of PVA-GNAs modified cement paste under different graphene dosages are shown in Fig.14 As shown in the figure, it can be seen that in the accelerated period (III) of hydration of PVA-GNAs modified cement paste, with the increase of graphene content, the exothermic peak intensity of silicate decreases and the peak appearance time is delayed. This phenomenon indicates that the nanofluid admixture inhibits the hydration reaction of calcium trisilicate (C3S) to a certain extent, which is one of the main reactions of cement coagulation and hardening. Since the hydration rate of C3S is slowed down, the heat released by the hydration reaction is reduced in the initial and accelerated period of cement coagulation, resulting in a decrease and delay in the heat flow peak. The high specific surface area and adsorption characteristics of graphene can weaken the interaction between water molecules and cement particles, thereby reducing the reaction rate. In addition, due to the physical barrier formed by graphene and PVA in the nanofluid admixture on the surface of cement particles, as well as their possible chemical interactions, these may lead to a slowdown in the dissolution of C3S and the subsequent formation of calcium silicate hydrate (CSH) and calcium hydroxide (CH).
[0122] In the deceleration period (IV), with the increase of graphene doping, the peak intensity of the sulfate depletion peak decreased and the time of peak appearance was delayed. This indicates that the incorporation of PVA-GNAs also delayed the solute reaction of tricalcium silicate (C3A) to form ettringite, and PVA-GNAs affected the interaction between C3A and sulfate. The reformation of ettringite increased significantly, while the rapid formation of monosulfate was completed in a shorter time. This is because the nucleation of graphene plays a more complex role in the sulfate hydration reaction. Since graphene provides additional nucleation sites, ettringite is promoted in the early stage, but with the increase of graphene doping, the blocking effect of acetate in PVA may become more significant, which affects the availability of water and sulfate, thereby reducing the intensity of the sulfate depletion peak in the later stage. It happens that this is also the period when the effect of different graphene doping on the hydration heat is most obvious. Therefore, the effect of nanofluid admixture on hydration during this period mainly affects the formation of two hydration products, ettringite and monosulfate.
[0123]
[0124] (-CH[OOC-CH3]-CH2-CH[OH]-CH2-) n +nH2O→(-CH[OH]-CH2-CH[OH]-CH2-) n +nCH3-COOH (Formula 7)
[0125] 2CH3-COOH+Ca(OH)2→Ca(OOC-CH3)2+H2O (Formula 8)
[0126] Among them, formula 7 is the main reaction and formula 8 is the side reaction.
[0127] Fig.14 It was observed that in the PVA-GNAs modified cement paste, the peak intensity of the sulfate depletion peak was higher than that in the blank group (without PVA-GNAs added). This was because the acetate produced by the presence of PVA had a blocking effect on the sulfate in the cement paste.
[0128] In addition, if Fig.15 The test results show that PVA forms a film on the surface of cement particles, which limits the reaction of sulfate. This blocking effect causes incomplete reaction of sulfate in the early hydration stage, resulting in an increase in the intensity of the sulfate depletion peak in the later stage.
[0129] The cumulative hydration exothermic curve of PVA-GNAs modified cement paste is as follows Fig.16 As shown in the figure, the results show that the total heat release of cement paste after adding PVA-GNAs is generally less than that of the blank group in the early stage of hydration. This is because the addition of PVA-GNAs slows down the initial rate of cement hydration reaction, especially affecting the hydration reaction of C3S and C3A, which are the main sources of cement hydration heat. When observing the final cumulative heat release, it can be seen that the total heat release decreases significantly with the increase of graphene content. This is because higher amounts of graphene enhance its effect on the hydration reaction, especially in the later stages of hydration. Because higher amounts of graphene not only affect the dissolution of C3S in the early stage of hydration, but also affect the hydration of C3A and its reaction with sulfate in the middle and late stages of hydration, thereby reducing the heat release during the entire hydration process. In addition, the analysis shows that PVA and graphene have a competitive relationship in their effects on cement hydration heat. PVA is mainly responsible for slowing down the hydration rate, while graphene promotes the hydration process to a certain extent by providing nucleation sites. With the increase of graphene content, these two effects are enhanced or antagonized to varying degrees, resulting in a complex nonlinear relationship.
[0130] In conclusion, the incorporation of PVA-GNAs has a significant effect on the cumulative heat release of cement hydration heat, which demonstrates the potential of PVA-GNAs as cement admixtures in regulating cement hydration heat and optimizing cement paste properties.
[0131] Similarly, this embodiment also uses CMC to prepare nanofluid admixtures (CMC-GNAs) with different graphene mass concentrations (0.07%, 0.14%, 0.28%, 0.42%, 0.64%, and 0.98%), and uses CMC-GNAs with different graphene mass concentrations to prepare CMC-GNAs modified cement pastes, and then provides hydration exothermic rate curves and cumulative hydration exothermic curves of CMC-GNAs modified cement pastes, such as Fig.17 shown. Fig.17 It shows that, whether it is PVA-GNAs or CMC-GNAs, with the increase of graphene content, both materials can delay the appearance time of the first and second exothermic peaks in cement paste and reduce the intensity of the exothermic peaks. This shows that the addition of nanofluid admixtures has a significant effect on the cement hydration kinetics, delays the hydration reaction, and reduces the rate of heat release. The difference is that during the modification process of PVA-GNAs, although the intensity of the second exothermic peak decreases with the increase of graphene content, its intensity is still higher than that of the blank group without nanofluid admixture. This reflects the competitive relationship between PVA and graphene, that is, there is a dynamic balance between the retarding effect of PVA and the nucleation sites provided by graphene. At certain dosages, although PVA reduces the hydration rate, the high specific surface area and nucleation ability of graphene are still sufficient to maintain a high exothermic intensity. CMC-GNAs show different behaviors from PVA-GNAs. The exothermic peak of cement paste with CMC-GNAs is lower than that of the blank group at all dosages, and the rate and intensity of hydration heat release are fully delayed with the increase of graphene dosage. This is because CMC, as a surfactant, provides stronger adsorption capacity and a more stable hydration reaction barrier compared with PVA. CMC-GNAs do not show a significant competitive relationship with graphene, but show a more synergistic effect between graphene and CMC, which makes CMC-GNAs more ideal in controlling hydration heat.
[0132] This synergistic effect is due to the following two reactions: On the one hand, the carboxyl groups in CMC can physically hinder the hydration reaction by adsorbing on the surface of cement particles and increasing the viscosity of the cement paste. On the other hand, the carboxyl groups of CMC form complexes with calcium ions, and the formation of the complex reduces the concentration of free calcium ions, thereby affecting the hydration rate, but does not significantly change the pH value. The reaction is:
[0133] (-CH2COONa-) (CMC) +Ca2+ →(-CH2COO-) (CMC) Ca+Na + (Formula 9)
[0134] Fig.17 (b) shows that with the increase of graphene content, the rising trend of the total hydration heat release is relatively slow. This shows that CMC-GNAs effectively delay the cement hydration reaction, especially at higher content, the rate of increase of heat release is low, showing its potential in controlling the development of hydration heat. Specifically, compared with the blank group without CMC-GNAs, CMC-GNAs also show the ability to reduce the rate of hydration heat release even at the lowest graphene content (0.07wt%). This delaying effect increases with the increase of content, especially at high content such as 0.64wt% and 0.92wt%. The slope of the cumulative heat release curve in the high content group is significantly lower than that in the blank group, which shows that CMC-GNAs play a key role in slowing down the early and middle hydration reactions. It should be noted that the hydration heat test time is 72h. Therefore, although the curve in the figure shows the heat release trend within 72h, the actual total amount of cement hydration heat release may still increase after the test time. The addition of CMC-GNAs showed a significant effect in reducing the total amount of cement hydration heat in the 72h hydration heat test, which not only slowed down the cement hydration reaction rate, but also helped to reduce the internal stress and crack risk caused by hydration heat.
[0135] In summary, although both PVA-GNAs and CMC-GNAs can effectively control cement hydration exotherm, CMC-GNAs provide a more balanced and comprehensive control effect. With the increase of graphene content, CMC-GNAs can more consistently delay the various stages of hydration reaction and reduce heat development.
[0136] Example 7 Application of nanofluid admixture in increasing fluidity and water retention of cement mortar
[0137] (1) Nanofluid admixtures (PVA-GNAs) with different graphene mass concentrations (0.02%, 0.04%, 0.06%, 0.08%, and 0.10%) were prepared using PVA solutions. The preparation method is described above.
[0138] (2) Adding PVA-GNAs to cement mortar to prepare modified cement mortar (referred to as PVA-GNAs modified cement mortar)
[0139] The modified cement mortar comprises cement, sand, water, defoamer TBP and nanofluid admixtures (PVA-GNAs) with different graphene concentrations, in parts by mass;
[0140] Among them, the mass ratios of the cement, sand, water, defoamer TBP and graphene in the nanofluid admixture are 1:3:0.45:0.006:0.02%, 1:3:0.45:0.006:0.04%, 1:3:0.45:0.06:0.075%, 1:3:0.45:0.006:0.08% and 1:3:0.45:0.006:0.10%, respectively.
[0141] The mixing process of PVA-GNAs modified cement mortar is as follows: cement and water are stirred at a low speed for 60 seconds → stirring is stopped for 60 seconds → nanofluid admixture, defoamer and standard sand are added → stirring at a low speed for 30 seconds → stirring at a high speed for 90 seconds → stirring is stopped → vibration is performed for 60 seconds.
[0142] The same method as above was used to prepare nanofluid admixtures (CMC-GNAs) with different graphene concentrations using CMC solution, and then CMC-GNAs modified cement mortar was prepared. The only difference from the above method was that PVA was replaced by CMC.
[0143] The flow rate of PVA-GNAs modified cement mortar and CMC-GNAs modified cement mortar was tested, and the results are as follows: Fig.18 As shown. Fig.18 As shown in (a), after the graphene production exceeds a certain concentration, the fluidity of the PVA-GNAs modified cement mortar gradually decreases with the increase of graphene content. This phenomenon can be attributed to the high specific surface area of graphene, which can absorb more water at the microscopic level, resulting in an increase in the water demand of the cement mortar. Although the micro-filling effect of graphene can theoretically reduce the water consumption of the cement mortar by filling the gaps between cement particles and replacing the water therein, the specific surface area of graphene is so large that its effect on increasing the water demand far exceeds the possible water reduction effect. This leads to the observation on a macro scale that the fluidity of the cement mortar decreases significantly with the increase of graphene content.
[0144] like Fig.18As shown in (b), the overall fluidity of CMC-GNAs modified cement mortar shows a trend of increasing with the increase of graphene content, and reaches a platform at 0.04% content, and then the fluidity has almost no significant change with the further increase of content. This characteristic is due to the water retention effect of CMC itself. It has the ability to form a water-absorbing film in cement mortar, which can lock water and reduce water evaporation and loss. Therefore, the addition of CMC helps to maintain the moisture in cement mortar, and maintain good fluidity even under the water absorption effect of the high specific surface area of graphene. Therefore, CMC-GNAs modified cement mortar may also improve water retention while optimizing fluidity, which is very beneficial in construction because it helps to reduce defects such as cracking and shrinkage caused by too fast evaporation of water.
[0145] Example 8 Application of nanofluid admixture in increasing the strength of cement mortar
[0146] In this embodiment, after curing the PVA-GNAs modified cement mortar and CMC-GNAss modified cement mortar prepared in Example 7 (including two ages of 7 days and 28 days), the PVA-GNAs modified cement mortar and CMC-GNAs modified cement mortar are poured into molds respectively, and plastic wrap is covered on the surface. Subsequently, it is placed in a constant temperature and humidity curing room with a curing temperature of 20°C and a curing humidity greater than 95%. After waiting for 24 hours, the molded test block can be demolded to obtain a formed test block. Then, after the test block is cured to the test age (such as 7 days and 28 days), the test block is taken out for testing (the curing in the present invention is carried out according to this method), and a 160mm×40mm×40mm prism parallel specimen is made, and then the compressive strength is tested. According to the provisions of GB-T17671-1999 "Test Method for Strength of Cement Mortar", when conducting the compressive strength test, the loading rate should be set to 2.4kN / s. The results are as follows Fig.19 As shown. Fig.19It can be observed in (a) that when the curing time was 7 days, the strength improvement of the PVA-GNAs modified cement mortar was not very significant (up to 23.00%) compared with the blank group. This is partly attributed to the retarding effect and air entraining effect of PVA, the latter of which increased the porosity of the mixture, and these voids hindered the potential role of graphene as a microfiller to improve density and strength in the early stage of hydration. As the curing time was extended to 28 days, the hydration degree of the cement mortar became more mature, and the microfilling effect of graphene was more fully reflected, resulting in a significant improvement in compressive strength. At the dosages of 0.02%, 0.04%, and 0.06%, the compressive strength showed similar levels, forming a plateau. This is because at these dosages, the interaction between graphene and PVA reached a dynamic equilibrium, and the effects of the two offset each other, resulting in little change in compressive strength. On the one hand, the retarding and air entraining effects of PVA limit the hydration rate, and on the other hand, the microfilling effect of graphene and the nucleation sites provided promote the formation of a denser structure. When the dosage was increased to 0.1%, a significant improvement in compressive strength (59.17%) was observed, indicating that at higher dosages, the micro-filling effect of graphene played a dominant role, specifically due to the formation of a more uniformly dispersed network structure in the cement matrix, which effectively improved the compressive strength. This distribution improves the quality of the interface transition zone (ITZ), thereby enhancing the overall performance.
[0147] like Fig.19 As shown in (b), for CMC-GNAs modified cement mortar, at low dosages, the compressive strength improvement after 7 days of curing is higher than that of PVA-GNAs modified cement mortar, specifically because CMC does not have the air entraining effect of PVA. The air entraining effect introduces tiny bubbles into the concrete, increasing its porosity, which may reduce the compressive strength in the early stage. Since CMC does not introduce additional gas, CMC-GNAs modified cement mortar can maintain a high initial compressive strength even at low dosages. When the curing age was 28 days, the compressive strength of CMC-GNAs modified cement mortars at each dosage was significantly improved compared with the blank group.
[0148] Therefore, it can be seen from the above results that the nanofluid admixture provided by the present invention can improve the compressive strength of cement mortar.
[0149] In this embodiment, the PVA-GNAs modified cement mortar and CMC-GNAs modified cement mortar prepared in Example 7 were cured (including two ages of 7 days and 28 days), and then made into 160mm×40mm×40mm prism parallel test pieces, and then the flexural strength was tested. According to the provisions of GB-T17671-1999 "Test Method for Strength of Cement Mortar", the loading rate should be set to 50N / s. The results are as follows: Fig. 20As shown, the nanofluid admixture provided by the present invention can significantly improve the flexural strength of cement mortar. Specifically, Fig. 20 As shown in (a) and (b), at a curing age of 7 days, the flexural strength of cement mortar with nanofluid admixtures is generally higher than that of the blank group (no nanofluid admixture added). This phenomenon is due to the relatively small retarding effect at low dosages and the insignificant delay effect on the hydration reaction. As a polymer, PVA can enhance the connectivity of cement mortar through its film-forming properties, because PVA can form a layer of polymer film between cement particles, which helps to transfer stress and improve the toughness of the mortar. At the same time, CMC, due to its polymer chain structure, acts as a "bridge" in the cement matrix, connecting cement particles and improving the stability of the overall structure. Since the concentration of PVA is higher than that of CMC at the same graphene dosage, the improvement of PVA-GNAs on the flexural strength is more significant at 7 days of curing. When the curing age is 28 days, the cement hydration is more complete. At this time, the synergistic effect of PVA, CMC and graphene is more prominent in improving strength. The peak values of flexural strength appear at dosages of 0.08% and 0.04%, respectively (increased by 30.64% and 25.83%, respectively). This is because as the hydration reaction proceeds, the amount of CSH gel and other hydration products formed in the cement matrix increases, which, combined with the micro-filling effect of graphene, further improves the toughness and crack resistance of the cement mortar. However, graphene is prone to agglomeration at higher dosages, which will destroy uniformity at the microscopic level and affect material properties. Relatively speaking, CMC-GNAs show the advantage of improving flexural strength at low dosages. This is because the special molecular configuration of CMC has a more obvious dispersion effect on graphene than PVA. Therefore, CMC-GNAs can play a good role at low dosages and show the advantage of improving flexural strength.
[0150] Example 9 Application of nanofluid admixture in promoting cement mortar to form interwoven fibrous hydration products, needle-like hydration products, and sheet-like hydration products
[0151] In this embodiment, the PVA-GNAs modified cement mortar in Example 7 was subjected to SEM testing after a curing period of 28 days. The SEM image is shown in FIG. Fig.21As shown in the figure. With the increase of graphene content, the flake hydration products (such as calcium hydroxide [CH]) in cement mortar become smaller and denser. This change indicates that the addition of graphene affects the morphology of hydration products and promotes the formation of hydration products with more compact structures. At a graphene content of 0.08%, the SEM images show a large number of fibrous and needle-shaped hydration products, such as calcium silicate hydrate (CSH) and calcium aluminate (AFt) or monosulfate (AFm). These fibrous and needle-shaped products are intertwined and form a composite structure around the flake CH. In addition, some blocky hydration crystals are observed to be attached to these fibrous and needle-shaped products. This "template effect" indicates that graphene can guide the growth mode of hydration products, thereby improving the density and mechanical properties of cement mortar. Combined with the previous hydration heat test results, it is speculated that in the sample doped with graphene, the hydration reaction generates a part of CSH and CH during the acceleration period, while the dissolution of C3A and the reaction with sulfate are delayed to the deceleration period. This delay leads to the formation of more intertwined hydration products, resulting in a stronger microstructure.
[0152] The SEM image of CMC-GNAs modified cement mortar after 28 days of curing age is shown in Figure 2. Fig. 22 As shown, similarly, intertwined fibrous and needle-like hydration products were formed.
[0153] The SEM test of CMC-GNAs modified cement mortar with a curing age of 7 days was carried out in the backscattering (BSE) mode at a scale of 100 μm. The results are shown in Fig.23 As shown, in the samples with intermediate doping amounts (e.g., Figure (c), 0.06%), a large number of flaky calcium hydroxide (CH) hydration products are shown. These flaky products form an interwoven composite structure with needle-rod-shaped hydration products, which may be calcium aluminate (AFt) or monosulfate (AFm). This structure shows that the addition of CMC-GNAs not only promotes the formation of flaky CH, but also may affect the morphology and distribution of other hydration products. These interwoven hydration products in the samples with intermediate doping amounts help to improve the structural compactness and mechanical properties of the material. The formation of flaky CH fills the micropores of the material, while the needle-rod-shaped hydration products increase the anchoring effect of the structure at the microscopic level, thereby improving the overall structural stability and bearing capacity of the material. As the graphene doping amount increases further, as shown in Figures (e) and (f), flaky and needle-rod-shaped hydration products can still be observed.
[0154] The SEM test of CMC-GNAs modified cement mortar with a curing age of 7 days was carried out in the backscattering mode at a scale of 500 μm. The results are shown in Fig.24 As shown in Figure 2, in the intermediate graphene doping sample, Fig.24As shown in (c), the fibrous calcium silicate hydrate (CSH) and needle-shaped calcium aluminate (AFt) or monosulfate (AFm) hydration products are more obvious. These slender fibrous CSH products are essential for the strength and toughness of cement-based materials because they are intertwined to form a dense network structure, which helps to improve the crack resistance and tensile resistance of the material. At the same time, the needle-shaped AFt or AFm products will be interspersed between the CSH fibers, further strengthening this microscopic network and improving the overall structural stability of the material. As the graphene content increases further, as shown in Fig.24 As shown in (e) and (f) in Figure 5, the distribution density of fibrous and needle-like hydration products seems to be reduced.
[0155] Example 10 Application of nanofluid admixture in reducing the cumulative pore volume of cement mortar after curing
[0156] After the CMC-GNAs modified cement mortar in Example 7 was cured for 7 days, a BET (Brunauer-Emmett-Teller) test was performed.
[0157] The relationship between the cumulative pore volume and pore size (adsorption branch) of CMC-GNAs modified cement mortar at 7 days of age is shown in the figure. Fig.25 As shown in (a), at a graphene content of 0.04%, the cumulative pore volume of the cement mortar sample is the lowest, indicating that graphene effectively fills the pores at this content and maximizes the density of the cement mortar. This is consistent with the above results, and the sample with a graphene content of 0.04% exhibits the highest flexural strength. These results are consistent with the above research conclusions, further confirming the effect of graphene content on the pore structure and mechanical properties of cement-based materials.
[0158] In cement-based materials, pores can be divided into the following categories according to the size of the pores:
[0159] Micropores: Pores with a diameter less than 2 nanometers. These pores are commonly found in adsorption materials such as activated carbon.
[0160] Mesopores: Pores with diameters between 2 and 50 nanometers. These pores have a significant influence on the mechanical properties and durability of materials, as they determine the hydration and strength growth of cement-based materials.
[0161] Macropores: Pores with a diameter greater than 50 nanometers. They generally reduce the strength of a material but can increase its thermal and acoustic insulation properties.
[0162] Harmful pores: generally refer to those pores larger than 200 nanometers. They are usually considered harmful because their large size may weaken the mechanical properties of the material.
[0163] The pore size distribution curve (adsorption branch) of CMC-GNAs modified cement paste after 7 days of curing is as follows: Fig.25 As shown in (b), 0.02% graphene shows a higher number of micropores less than 4nm. The distribution and connectivity of micropores and mesopores in the material determine the transport capacity of water, solutes and reaction products during the hydration process, which directly affects the strength and durability of cement paste. This is consistent with the test results that 0.02% graphene yield showed the highest compressive strength ( Fig.18 (b)). For 0.10% graphene doping, there are fewer small-volume mesopores, indicating that at higher doping levels, excessive increase in graphene leads to agglomeration, thereby hindering the pore filling process. Graphene agglomeration can form larger aggregates, which may form macropores at the microscopic level. These macropores are not conducive to improving the mechanical properties of the material. Therefore, graphene at high doping levels may cause the pore structure to deteriorate, thereby affecting the macroscopic properties of the material.
[0164] Example 11 Application of graphene nanofluid in reducing the penetration of chloride ions in cement mortar after curing
[0165] After curing the PVA-GNAs modified cement mortar in Example 7 for 28 days, a test block with a volume of 160 mm × 40 mm × 40 mm was obtained. The test block was then placed in a 5% NaCl solution. After 60 days and 120 days of salt water immersion, the relationship curve between the chloride ion concentration in the test block and the corresponding depth is shown in the following figure: Fig.26 As shown. Fig.26 As can be seen from (a) in the figure, with the increase of graphene content, the diffusion trend of chloride ion concentration in the test block shows a downward trend. Specifically, with the increase of depth, the chloride ion concentration of all test blocks gradually decreases, which indicates that chloride ions gradually diffuse into the interior of the test block. Moreover, with the increase of graphene content, the initial concentration of chloride ions also decreases, indicating that PVA-GNAs enhance the resistance of cement mortar to chloride ions. Fig.26 As can be seen in (b), the concentration of chloride ions also decreases significantly at deeper measurement points. In addition, as the amount of graphene increases, the rate of decrease in chloride ion concentration slows down, which is related to the dispersed network structure formed by graphene in cement mortar.
[0166] The measured chloride ion diffusion coefficient is as follows:
[0167] Table 1. Chloride ion diffusion coefficient of PVA-GNAs modified cement mortar tested by salt water immersion method
[0168]
[0169] The chloride diffusion coefficient decreased significantly with increasing PVA-GNAs (i.e. graphene) dosage over the 60-day and 120-day test periods, indicating that the addition of the nanofluid admixture significantly increased the density of the cement mortar and reduced the chloride permeability. Specifically, the layered structure of graphene increases the path length of chloride ions through the cement mortar, improving the barrier properties. This effect became more pronounced over time, specifically due to further hardening of the cement mortar. In addition, the decrease in surface chloride concentration (Cs) with increasing dosage also indicates that graphene has a strong adsorption effect on chloride ions, thereby reducing the accumulation of chloride ions on the surface. R 2 Values close to 1 indicate a good fit to the experimental data.
[0170] Based on the above test results, we can know that:
[0171] (1) PVA and CMC, as dispersants of graphene, significantly affected the setting time of cement paste after introduction. The introduction of PVA prolonged the setting time, especially in PVA-GNAs modified cement paste, the final setting time was prolonged more significantly. This shows that although the nucleation effect of graphene helps to accelerate the hydration reaction, the retarding effect of PVA dominates in the later stage of the hydration reaction, especially with the increase of graphene content, this effect becomes more obvious.
[0172] (2) Regarding the influence of hydration heat, PVA-GNAs and CMC-GNAs modified cement pastes showed different control effects. PVA-GNAs modified cement significantly reduced the hydration heat at high dosage, slowed down the hydration reaction rate, and especially affected the hydration of C3S and C3A. CMC-GNAs modified cement also showed that the increasing trend of the total hydration heat was effectively slowed down with the increase of dosage, especially at higher dosage, the rate of increase of heat release was relatively low, showing its significant role in slowing down the hydration reaction.
[0173] (3) In terms of fluidity and mechanical properties, nanofluid admixtures improve the fluidity and mechanical properties of cement mortar, and the micro-filling effect of graphene and its interaction with the cement matrix enhance the toughness and crack resistance of the material.
[0174] (4) Effect on the microscopic hydration products of cement mortar. The results show that with the increase of graphene content, the structure of hydration products in cement mortar becomes smaller and denser, and the fibrous (AFt) and needle-like hydration products (such as calcium silicate hydrate [CSH] and calcium aluminate [AFt] or monosulfate [AFm]) are intertwined, which enhances the density and mechanical properties of the material.
[0175] (5) The introduction of nanofluid admixture significantly changed the pore structure of cement mortar, especially promoted the development of micropores and mesopores. When the dosage was 0.02% and 0.04%, the pore structure of the sample was obviously refined and filled.
[0176] (6) The introduction of nanofluid admixtures significantly reduces the chloride ion diffusion coefficient, which indicates that nanofluid admixtures have the potential to improve the durability of cement mortar, especially to reduce the penetration of chloride ions into the interior through the microscopic pore network.
[0177] The above indicates the effectiveness and potential of the nanofluid admixture provided by the present invention as a nanofluid admixture for cement-based materials in improving setting time, controlling hydration heat, optimizing pore structure, and improving mechanical and durability properties.
[0178] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A method for preparing a nanofluid admixture, characterized in that: The nanofluid additive comprises water, graphene dispersed in the water, and a dispersant, wherein the dispersant comprises polyvinyl alcohol and / or sodium carboxymethyl cellulose. The preparation method of the nanofluid additive comprises the following steps: Provide graphite powder and dispersant; Adding the dispersant into water and stirring to obtain a dispersant solution; Adding the graphite powder to the dispersant solution, and then sequentially performing shear exfoliation and emulsification exfoliation to obtain a mixed solution; After the mixed solution is centrifuged, the supernatant is collected to obtain the nanofluid additive.
2. The preparation method according to claim 1, characterized in that: The concentration of the dispersant in the dispersant solution is 5 to 25 g / L.
3. The preparation method according to claim 1, characterized in that: The rotation speed of the shearing peeling is 10000 rpm, and the time of the shearing peeling is 3 to 21 minutes.
4. The preparation method according to claim 1, characterized in that: The rotation speed of the emulsification peeling is 6000 rpm, and the time of the emulsification peeling is 20 to 180 minutes.
5. The preparation method according to claim 1, characterized in that: The rotation speed of the centrifugation is 10000 rpm, and the time of the centrifugation is 30 to 80 minutes.
6. The preparation method according to claim 1, characterized in that: The time for the shear peeling is 12 minutes, the time for the emulsification peeling is 120-140 minutes, and the time for the centrifugation is 30 minutes.
7. A nanofluid admixture, characterized in that: The preparation method is described in any one of claims 1 to 6.
8. An application of the nanofluid admixture according to claim 7, characterized in that: The nanofluid admixture is applied to cement-based materials, and the cement-based materials include one of cement paste, cement mortar and concrete.
9. A modified cement-based material, characterized in that: The modified cement-based material includes one of modified cement paste, modified cement mortar and modified concrete; The modified cement paste comprises cement, water and the nanofluid admixture according to claim 7; The modified cement mortar comprises cement, sand, water and the nanofluid admixture according to claim 7; The modified concrete is prepared from the modified cement paste or the modified cement mortar.
10. The modified cement-based material according to claim 9, characterized in that: In the modified cement paste, the mass ratio of the cement, water and graphene in the nanofluid admixture is 1:(0.45-0.55):(0-0.002); In the modified cement mortar, the mass ratio of the cement, sand, water and graphene in the nanofluid admixture is 1:(2-4):(0.45-0.55):(0-0.002); In the modified cement paste and the modified cement mortar, the mass of the graphene in the nanofluid admixture is not 0.
Citation Information
Patent Citations
Liquid-phase stripping preparation method of graphene
CN105502371A
Modified graphene oxide cement concrete early strength agent and application thereof
CN106007450A
Cement concrete durability reinforcing additive
CN107337363A
High-performance graphene concrete and preparation method thereof
CN109020416A
Graphene modified cement-based composite material and preparation method thereof
CN109553366A
Cited By
Application of nanofluid admixture in concrete
CN118745089A
Application of nanofluid admixture in mortar
CN118745090A
Application of nanofluid admixture in neat paste
CN118930113A